2018
DOI: 10.6002/ect.2016.0342
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Persistent secondary hyperparathyroidism is common after successful kidney transplant, with concomitant hypercalcemia and hypophosphatemia potentially leading to reduced graft survival and increased cardiovascular risk. Cinacalcet, a calcimimetic agent that activates the calcium-sensing receptors in parathyroid glands, is a therapeutic option. In this study, we assessed the long-term treatment effects of cinacalcet for a period of up to 5 years in a cohort of kidney transplant recipients. Key word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Cinacalcet appears to be a promising therapeutic option for patients with persistent hypercalcemia post transplantation at least as a bridging agent before parathyroidectomy. [848586]…”
Section: Persistent Hyperparathyroidism After Kidney Transplantationmentioning
confidence: 99%
“…Cinacalcet appears to be a promising therapeutic option for patients with persistent hypercalcemia post transplantation at least as a bridging agent before parathyroidectomy. [848586]…”
Section: Persistent Hyperparathyroidism After Kidney Transplantationmentioning
confidence: 99%
“…The intact PTH level decreased by 7.68 pmol/L at 6 months (P not significant); however, intact PTH level decreased further by 20.07 pmol/L at the end of follow up ( p < 0.01). Serum phosphate level increased significantly and eGFR remained stable throughout follow-up [ 39 ].…”
Section: Medical Management and Treatment Options Of Persistent Post-mentioning
confidence: 99%
“…Zavvos et al also conducted a study including the results of a five-year follow-up with cinacalcet treatment. They also showed that calcium decreased significantly, phosphorus increased, PTH levels decreased over time, and renal functions were preserved [ 17 ].…”
Section: Discussionmentioning
confidence: 99%